1979
DOI: 10.1016/0008-8749(79)90173-4
|View full text |Cite
|
Sign up to set email alerts
|

Localization of human antigen-specific helper and suppressor function in distinct T-cell subpopulations

Abstract: Distinct human T-cell subpopulations were isolated and cultured in the presence of B-cells and antigens. After an incubation period of 6 days cells were tested for their capacity to secrete antigen-specific antibodies in the PFC-assay. The results indicate that the T-helper activity for the antigen-induced T-dependent B-cell differentiation is located in the Tp-subpopulation, whereas the suppressor-cell activity is confined to the Ty-subpopulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
2

Year Published

1980
1980
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 23 publications
(22 reference statements)
1
23
0
2
Order By: Relevance
“…The previous studies on antigen-induced T cell help in the human system have been "conflicting," with some investigators noting radiation sensitivity and others noting a radiation resistance to antigen-induced T cell help (10,25). The data present in this study using an antigen-specific system have confirmed the earlier observations on the effect of irradiation on PWM-induced T cell help and have provided evidence that the T cell involved in antigen-induced, antigen-specific antibody production is, in contrast to some earlier reports (8,10,25), exquisitely sensitive to radiation. Irradiation can have a number of effects on the expression of cellular function.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The previous studies on antigen-induced T cell help in the human system have been "conflicting," with some investigators noting radiation sensitivity and others noting a radiation resistance to antigen-induced T cell help (10,25). The data present in this study using an antigen-specific system have confirmed the earlier observations on the effect of irradiation on PWM-induced T cell help and have provided evidence that the T cell involved in antigen-induced, antigen-specific antibody production is, in contrast to some earlier reports (8,10,25), exquisitely sensitive to radiation. Irradiation can have a number of effects on the expression of cellular function.…”
Section: Discussionsupporting
confidence: 51%
“…Unfortunately, there have been conflicting data among sev-. eral of these systems (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Of particular note has been the divergence of results with regard to the radiosensitivity of T cell help and the relative contributions of allogeneic effects in the mitogen-induced vs. antigen-induced human B cell systems.…”
Section: Introductionmentioning
confidence: 99%
“…Human PBMCs were prepared by Ficoll-Hypaque gradient centrifugation from healthy blood donors, and T lymphocytes were isolated by rosetting with 2-amino-ethylisothiuronium-treated sheep red blood cells (Heijnen et al, 1979). T lymphocytes were cultured overnight in culture medium (RPMI 1640 supplemented with 10% fetal bovine serum, 2 mM glutamine, and antibiotics) to remove erythrocyte ghosts.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that T cell factors of murine origin can be absorbed on human PBL of certain donors (27) and, vice versa, human T cell factors were shown to activate murine B cells for antibody production (21,28). Heijnen and coworkers (29,30) have demonstrated collaboration between human helper T cell factors and human B cells; however, they worked with antigenic systems to which the response is not genetically controlled and all individuals were expected to respond to them.…”
mentioning
confidence: 99%